A English Teachers Skill in Using the Canva Application as a Learning Media at SMK Assalaam Bandung - Rosliyani, Mira (NextGen Education Review Journal, 2025)
In this era of globalization, teachers are required to become professional teachers. Professional teachers certainly have competencies that show their quality in teaching. These competencies are manifested in the form of mastery of knowledge, skills, and professionalism in carrying out as a teacher. One of the skills that teachers must have is the skill of using learning media so that the teaching and learning process is not monotonous and can attract students' attention. Of the many learning media available, Canva is one of the digital visual applications that provides various kinds of learning media. With this, this study was conducted to determine the skills of English teachers in using the Canva application as a learning medium at SMK Assalaam Bandung. In this study, the researcher revealed that teachers at the school were already proficient in using the Canva application as a learning medium. This is evidenced by the special training attended by teachers. Canva is effectively used for learning media, which is proven to increase students' interest in learning and students become interactive during the learning process.